EFEKTIVITAS PEMBELAJARAN SERVIS BAWAH PERMAINAN BOLAVOLI BERBASIS MULTIMEDIA DI SMA YP YAQLI OKU TIMUR SUMATERA SELATAN - Muhsana Elcintami Lanos; Hikmah Lestari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This research uses quantitative methods. This study aims to determine the effectiveness of implementing multimedia-based volleyball game underhand learning in class X High School (SMA). The research design in this study was one control group pretest-posttest. The research was conducted at SMA YP Yaqli OKU Timur, South Sumatra. Based on the results of the test of the effectiveness of the application of multimedia-based volleyball underhand learning in class X High School (SMA) that has been carried out, the results of the N-Gain Score test on the learning outcomes of volleyball underhand serve obtained an average N-Gain Score for the class experiment of 93.5% in the